A fotografia na psicologia: metassíntese de teses e dissertações brasileiras - Santos Júnior, Paulo Sérgio dos (2018)
In this research metasynthesis was realized about the uses of photography in psychological research. The objective are: explore, systematize, describe and configure the historic, geographic and institutional constitution; identify theoretical and methodological aspects that subsidize the knowledge produced with the use of photography and interpret the uses of photography in psychological research produced in graduate programs brazilian in psychology. To reach these objectives, four methodological stages developed were, denominated: Exploration, Refinement, Description and Interpretation. For data search has used the Banco de Teses & Dissertações da CAPES and Plataforma Sucupira, from the descriptors: fot* AND Psicologia. In the first part of this study, realized descriptive analysis of 292 documents (230 dissertations and 62 theses) about the categories: academic degree, historic series, geographic and institutional distribution. The data been were related and compared with information about the brazilian graduate programs, available in the georeferencing tool of the CAPES – GeoCAPES. The results show, quantitatively, are more production on the level of the master degree, proportionally to greater quantitative of graduate programs with an offer of this academic degree, including in the area of Psychological. The information’s also indicates that continuous growth and high of the production, whom presents as justification, the expansion of the brazilian graduate programs, verified during the beginning of the past decade (2000-2009). In addition, been identified productions distributed in all the Brazilian regions. The states of São Paulo, in particular, a University of the São Paulo and Pontifical Catholic University of the São Paulo presents greater number of the productions. However, should considered the greater time of the existence of the graduate programs these institutions, aspect that may indicative of the greater number of the productions in these academic venues. In total, been located theses and dissertations arising of the 19 federative units distributed in 42 institutions of the higher education. The second part of this study, realized the interpretative synthesis, moment whereby proceed the qualitative analysis of the 50 theses were been located in full. Corroborated with the traditional literature, when affirm that objective of the photography in Psychology is the attribution of meanings. At context in the works analyzed, identified use as recording, visual stimuli and auto-photographic. Added to these, the use as iconographic collection, when the photographs are redeemed as sources of historical information and, also, the production of imagery contents, for this purpose, aim construction databases, to the validation and update of the projective instrument to the brazilian context or due to third parties copyright images. Finally, the uses as mediator object, when photography is used as a facilitator of dialogue in the process of knowledge construction. At context this use, researchers and interlocutors has access to a multifaceted object: memory support, mediating materiality in the psychotherapeutic attendance and group context, translation work among others. We concludes that the photography, in general, is applied collaborative the other tools because it allows the researcher deepen the knowledge about the object of study. In addition, the photography shows a multifaceted feature can be applied to various types of search: historical analysis, empiric research, ethnography, cartography, etc. Regarding the contributions to the development the metasynthesis, its stands out the advance achieved in this study, into consideration of the historic description and detailed of the analytic corpus of the research.